The role of natural soundscape in nature-based tourism experience: an extension of the stimulus–organism–response model. Issue 5 (4th March 2022) - Jiang, Jinde
ABSTRACT : This paper echoes the call for multisensory tourism research from the perspective of auditory sensory experience. Based on an extended stimulus–organism–response (SOR) model, the natural soundscape is linked with tourists' emotion and behaviour, and the possible structural relationships between them are verified with structural equation modelling. The results indicate that auditory factors such as natural soundscape significantly affect tourists' emotion and behaviour in nature-based tourism. Emotion induced by natural soundscape can significantly improve tourists' actual approach behaviour and behavioural intention in nature-based tourism. Different emotional dimension can elicit different behavioural type. Emotional arousal tends to trigger tourists' actual approach behaviour, whereas emotional pleasure tends to encourage tourists' behavioural intention. Actual approach behaviour in natural soundscape can significantly promote tourists' behavioural intention. Based on these findings, valuable information for tourism managers on generating desirable tourist emotion and behaviour is offered.